Existence of English Meeting Club in Supporting the English-Speaking Skill of University Students: Their Constructive Voices - Maming, Khadijah; Sianna; Hasman; Maria Elaine A Cabuso; Eka Sasmita (Eduvelop: Journal of English Education and Development, 2024)
This study aimed to find out the students’ perception on English meeting club to support their English-speaking skill. The subject of this study were students at Institut Agama Islam Negeri (IAIN) Parepare who are the members of English meeting club in LIBAM (Lintas Imajinasi Bahasa Mahasiswa). This study was case study of descriptive qualitative. There are seven students participated as research respondent. This study used interview as a research instrument. From the result of interview, majority of students had the perception that the English club was able to improve their speaking skill. They experienced development when speaking English in English meeting club such as no longer filler words anymore, can pronounce words properly, speaking correctly and know more about grammar. In addition, after joining English meeting club, they become more confident to speak in front of people. They also taught and trained to teach English at the junior and senior high school which is called TOT (Training of Trainer) in preparation for becoming tutor in the school-built program and English camp provided by LIBAM in several schools. The researchers concluded that the students had the perception that the English club was able to improve and support in developing English speaking skill. They are also more interested being taught by cheerful tutors in informal situations preferred in regular class, so the English meeting club provides students with a place to practice speaking English well without fear of making mistakes and it is appropriate media to improve students' speaking skill.